Diagnostic utility of real-time RT-PCR for chikungunya virus detection in the acute phase of infection: a retrospective study - Anupama Sajith; Varsha Iyengar; Prasad Varamballi; Chiranjay Mukhopadhyay; Sudheesh Nittur (Annals of Medicine)
Background Chikungunya fever is a viral disease spread by Aedes mosquitoes, reported in over 110 countries. In India, it was first detected in Kolkata in 1963 and is now widespread. Diagnosis often relies on detecting anti-chikungunya IgM antibodies, but these may not be present during the acute phase as viremia can last up to 8 days, leading to underreporting. The present study aims to assess the diagnostic use of real-time RT-PCR for detecting chikungunya-specific nucleic acid in serum samples during the early stages of infection.Methodology A retrospective cross-sectional study was conducted using archived samples collected as a part of ‘the hospital-based Acute Febrile Illness (AFI) surveillance project’. AFI cases having fever ≤8 days and arthralgia without any aetiology between 2016 and 2018 from Karnataka, Kerala, and Tamil Nadu were included in the study. Samples were subjected to nucleic acid extraction followed by chikungunya real-time RT-PCR using a standardized in-house protocol. The samples that tested positive for Chikungunya by real-time RT-PCR were further tested for detecting anti-Chikungunya IgM antibodies using enzyme-linked immunosorbent assay. Demographic characterization of the cases was performed using SPSS version 20 and GraphPad Prism version 10.Results Out of a total of 646 samples tested, 31 samples (4.79%) were positive by real-time RT-PCR for chikungunya virus, 20 of which had a Ct value of <30, indicating a relatively high viral load. Among the 31 serum samples tested for anti-Chikungunya IgM antibodies, only one showed a positive result. Demographic analysis showed that 67% of cases were male and 32% were female, respectively. Clinical data analysis showed that most of the cases presented with cough (87%), headache (80.6%), myalgia (77.4%), coryza (70.9%), vomiting (58%), and abdominal pain (38.7%).Conclusion The current study findings highlight the importance of screening patients with fever for up to 8 days and arthralgia for not only detecting IgM antibodies against chikungunya using ELISA but also for chikungunya virus-specific nucleic acid through real-time PCR/nucleic acid amplification techniques, or other methods. Not performing laboratory tests to screen for chikungunya-specific nucleic acid or antigen may result in underreporting of chikungunya cases, thereby impacting effective control measures and management of cases.